INTEGRATION OF INTERACTIVE MEDIA INTO FOREIGN LANGUAGE LEARNING TO SUPPORT EFFICIENCY OF STUDY PROCESS - Kuprienė, Laima; Žegunienė, Vaida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Contemporary society is actively engaged into technology innovations due to their multi-purposeful usage for personal, professional and educational reasons. Many new terms defining information communication technologies appear but the paper focuses on the interactive media, which may be considered as an integral part of the phenomenon. It is aimed to analyze and discuss the possibilities of integration of interactive media into language learning process to support the efficiency of the study process taking into consideration the needs and achievements of students. The lectures organized with traditional teaching material are getting old-fashioned gradually; therefore, new trends appear in the education process and technologies have to be successfully integrated by the teachers working in higher education institutions. Currently life pace is extremely fast, and rapid changes influence the life of young people who want to be well-educated and prepared for the further professional career. The research was organized to investigate whether the students of higher education institution demonstrate willingness to integrate interactive media into language learning process, i.e. students do not have to be passive users but actively apply and use interactive media in the learning process. Consequently, the teachers have to be familiar with the opportunities provided by the interactive media and acknowledge the necessity of its integration, but still some considerations and uncertainty exist. The methods used for the research are as follows: analysis of the scientific literature sources, content analysis, and questionnaires. Findings of the research are formulated after analysis of the collected data and they revealed the capabilities of the students to use interactive media and perception of the importance and usefulness of such measures.Majority of teachers demonstrate conservative attitude towards innovations and implementation of modern teaching/learning methods, but the situation will be improved putting the efforts in order to seek positive learning outcomes and modernize the study process.